Identification and Management of Ascochyta Blight of Chickpea (Cicer arietinum L.) Prevalent in Bundelkhand Region of Uttar Pradesh, India - Upadhyay, Utkarsh; Prasad, Durga (International Journal of Bio-resource and Stress Management, 2023)
Field investigations were carried out during rabi (October–March), 2020–21 and 2021–22 in major chickpea-growing areas of Banda, Mahoba, Hamirpur and Chitrakoot districts of Bundelkhand region of Uttar Pradesh, India to find out a suitable management strategy for ascochyta blight disease in standing crop conditions. A survey study was carried out during January–February, 2022 to find out the occurrence of ascochyta blight. The overall severity of ascochyta blight observed in four surveyed districts ranged between 15.82–17.50%. The pathogen exhibited floccose and white to pale olive colored colony with irregular white periphery on potato dextrose agar media after 14 days of incubation. Maximum growth (46.2 mm) of mycelia was recorded on oatmeal agar media followed by the growth of 43.2 and 40.4 mm obtained in malt extract agar media and potato dextrose agar media, respectively. In standing crop conditions, two sprays of combination of Tebuconazole 50%+Trifloxystrobin 25% WG @ 0.1% gave the maximum reduction in disease incidence (47.05%) and disease severity (63.86%) along with the highest enhancement in grain yield (54.81%), number of pods plant-1 (55.56%) and 100 grain weight (62.28%). Results revealed that ascochyta blight of chickpea was prevalent in Bundelkhand region of Uttar Pradesh. Oatmeal agar medium can be used for cultivation of Ascochyta rabiei. In field, ascochyta blight can be managed by two sprays of combination of Tebuconazole 50% + Trifloxystrobin 25% WG @ 500 g ha-1 at symptoms initiation and after 15 days of first spray.